Phonological Errors of Broca’s Aphasia: A Single Case Study of Neurolingusitics (e-Journal of Linguistics, 2019)
Broca’s aphasic patients display language problems in initiating utterances withgroping movements, multiple false attempts and self-correction resulting from a lesion to thethird frontal convolution of the left hemisphere of the brain. This study describes the forms ofsound impairment, types of errors and phonetic processing by a Balinese patient who sufferedfrom non-fluent speech disorder. The results showed that KW’s speech performance wascategorized severe. There were 0.80% phonological errors in word naming, 0.92% in picturenaming, 0.87% in answering questions and 0.89% in oral reading. Of the three other types oferrors, sound substitution errors mostly appeared in every phonological task. He made 65%sound substitutions, 20% sound distortions, 10% sound insertions and 5% omissions. Differentspeech stimulation could trigger sound inconsistency. The phonological errors occurred becausethere was not any appropriate coordination between phonological representation and phoneticrealization due to the loss of linguistic message in Broca’s area.
Keywords: aphasia; language modality; lexical access